Pathomorphological changes in the lungs of Red-eared turtles (Trachemys scripta elegans (Wied, 1839)) with pneumonia and in the liver at parenteral administration of Ceftiofur - Chuliuk, V.; Dankovych, R. (Scientific Progress & Innovations, 2023)
Pneumonia is quite common in reptiles, and antibiotics, including cephalosporins, are widely used in its treatment. The study was aimed to investigate the pathomorphology of heterophilic pneumonia in Red-eared freshwater turtles (Trachemys scripta elegans (Wied, 1839)), as well as to study the pathomorphological changes that develop in the liver of turtles after parenteral administration of Ceftiofur. The turtles of the experimental group 1 (n=3) developed heterophilic pneumonia. The Red-eared turtles of the 2-nd experimental group (n=3) were administered 2.2 mg/kg of Ceftiofur daily intramuscularly. Specimens for histological and ultrastructural studies were collected on day 14 of the experiment. Histological sections were made using a sled microtome and a cryostat microtome, stained with a hematoxylin and eosin, and Sudan III. Electron microscopic examination was performed using a PEM-100-01 electron microscope. As a result of the study, it was found that in Red-eared turtles with the development of heterophilic pneumonia, there is an accumulation of exudate in the lumen of the fovea, which contains a significant number of heterophils, erythrocytes, macrophages, and plasma elements. It was found that the introduction of therapeutic doses of Ceftiofur in the liver develops hyperemia of venous vessels of different sizes, dystrophic changes in hepatocytes, as well as necrotic changes in single cells of the liver parenchyma, a decrease in the content of neutral fats in the cytoplasm of hepatocytes, and a decrease in the density of the melanocrophage complexes. Transmission electron microscopy of the liver revealed dilation of the tubules of the granular endoplasmic reticulum of hepatocytes, swelling of mitochondria, destruction of their crusts, and a decrease in the content of glycogen granules in the hepatocyte cytoplasm. Thus, it has been determined that the development of heterophilic pneumonia in red-eared freshwater turtles is accompanied by the development of a vascular reaction in the lungs and the predominance of the exudates of heterophiles. After the introduction of therapeutic doses of Ceftiofur, alternative changes in hepatocytes develop in the liver, and discriminative changes are recorded in the vascular system of the liver.